Pola Zonasi dan Keragaman Jenis Penyusun Vegetasi Mangrove Di Desa Sidodadi, Kabupaten Pesawaran Lampung - Ansoridani, Hafiz (Wanamukti: Jurnal Penelitian Kehutanan, 2023)
Mangrove zoning describes the stages of succession that is in line with changes in site factors. Changes in the site and the adaptability of mangrove species to site status could determine the species of mangrove vegetation constituent. The objectives of the study were to determine the species constituent of mangrove vegetation, the index of species diversity and the formation of mangrove forests in Sidodadi Village, Teluk Pandan District, Pesawaran Regency, Lampung. Cluster sampling was employed as the sampling method. In each cluster, observation stations are placed as checkered lines as sample plots. The composition of the mangrove species’ vegetation was analyzed using descriptive analytic methods, and mangrove zoning was determined by grouping the dominant species and comparative analysis. The diversity index was analyzed using the Shanon-Wiener diversity index. The results showed that 21 plant species from 12 families comprise Pesisir Pesawaran mangrove vegetation. Of the 21 species, 10 are true mangroves, and 11 are classified as mangroves associates. The diversity of mangrove species in the Pesawaran Coast is in the moderate category (Shanon-Wiener) with a species diversity index value of 1.942. There are two mangrove zones in the Pesawaran Coastal area, namely the mid-mangrove zone, which is dominated by the Rhizophoraceae family, and the hinterland mangrove zone, which is dominated by associates mangrove groups.